Prevalensi dan Intensitas Telur Cacing Parasit pada Feses Sapi Bali (Bos javanicus domesticus) di Peternakan Desa Kertabuana Kec. Tenggarong Seberang dan Desa Muang Lempake Kec. Samarinda Utara - Wesley, Sitohang; Trimurti, Sus; Fadhila, Fasya; Patang, Fatmawati; Hariani, Nova (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The research was conducted from May to August 2015. The purposes of the research are to determine the prevalence and intensity of gastrointestinal worm infection in bali cattle, to know wether there is difference in the number of gastrointestinal worm eggs that are found in of male and female bali cattle, to find out if there is a difference in the prevalence and intensity of gastrointestinal worm infection of bali cattle in kertabuana and Muang village. The total number of faecal samples were collected from bali cattle at 2 ranches with are repetition. The results showed that there are 13 spesies of worm eggs found in the feces, which are Ascaris lumbricoides, Bunostomum phlebotomum, Dicrocoelium dendriticum, Echinicoccus granulosus, Fasciola hepatica, F. gigantica, Haemonchus contortus, Hymenolepis nana, H. diminuta, Ostertagia ostertagi, Paramphistomum cervi, Schistosoma bovis, Trichuiris globulosa. Fasciola hepatica worm eggs have the highest prevalence, infecting bali cattle in both ranches with a percentage of 56,67% in Muang village and 83,33% in Kertabuana village. Ascaris lumbricoides also has the second highest intensity after F. hepatica worm eggs in both ranches with 200 eggs/gram of feces in Muang village and 300 eggs/gram of feces in Kertabuana village.